2020
DOI: 10.1029/2020jd032856
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Signals in 1‐min Observations of Overshooting Tops and Lightning Activity in a Severe Supercell Thunderstorm

Abstract: This work examines a severe weather event that took place over central Argentina on 11 December 2018. The evolution of the storm from its initiation, rapid organization into a supercell, and eventual decay was analyzed with high-temporal resolution observations. This work provides insight into the spatio-temporal co-evolution of storm kinematics (updraft area and lifespan), cloud-top cooling rates, and lightning production that led to severe weather. The analyzed storm presented two convective periods with ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 65 publications
(85 reference statements)
0
10
0
Order By: Relevance
“…Concurrent with the 1-min multispectral imagery, the GOES-East Geostationary Lightning Mapper (GLM) collected continuous total lightning (in-cloud and cloud-to-ground) event, stroke, and flash data throughout the day and night with 2-ms temporal resolution and 8-km spatial resolution (Rudlosky et al 2018). The rapid evolution of GOES-identified overshooting tops, radar, and spaceborne and ground-based lightning structure in a severe hailstorm during RELAMPAGO is examined in Borque et al (2020). During RELAMPAGO at São Borja, five intense convective episodes were observed (Table 5).…”
Section: (E) Lightningmentioning
confidence: 99%
“…Concurrent with the 1-min multispectral imagery, the GOES-East Geostationary Lightning Mapper (GLM) collected continuous total lightning (in-cloud and cloud-to-ground) event, stroke, and flash data throughout the day and night with 2-ms temporal resolution and 8-km spatial resolution (Rudlosky et al 2018). The rapid evolution of GOES-identified overshooting tops, radar, and spaceborne and ground-based lightning structure in a severe hailstorm during RELAMPAGO is examined in Borque et al (2020). During RELAMPAGO at São Borja, five intense convective episodes were observed (Table 5).…”
Section: (E) Lightningmentioning
confidence: 99%
“…In particular, several recent studies are being made based on the RELAMPAGO field-campaign data (Nesbitt et al 2021). For example, Borque et al (2020) (hereafter B20) examined the evolution of a convective cell that took place on 11 December 2018, using the operational weather radar located in Córdoba City which is part of the Argentinean National System of Meteorological Radars (De Elía et al, 2017), and the spatio-temporal distribution lightning strikes derived from the RELAMPAGO 3D Lightning Mapping Array (LMA) and the Geostationary Lightning Mapper (GLM) on board of the GOES-16 satellite. They found that a decrease in cloud top temperature (CTT) and an increase in the lightning activity precede two convective periods with associated severe weather.…”
Section: Introductionmentioning
confidence: 99%
“…Borque et al. (2020) compared the cloud‐top temperature and lightning activity in severe thunderstorms and found that the LJs in the GLM lightning observations provided a 20‐min lead time for the second convection core.…”
Section: Introductionmentioning
confidence: 99%
“…By applying the GLM in the LJ algorithm, it was found that 15 out of 25 GLM jumps were accompanied by a subsequent radar intensity increase (Curtis et al, 2018) and in a further study of 930 storms showed a Probability of Detection of 68% and False Alarm Rate of 82% (Curtis, 2018). Borque et al (2020) compared the cloud-top temperature and lightning activity in severe thunderstorms and found that the LJs in the GLM lightning observations provided a 20-min lead time for the second convection core.…”
mentioning
confidence: 99%